Andrographolide Protects against Aortic Banding-Induced Experimental Cardiac Hypertrophy by Inhibiting MAPKs Signaling - Wu, Qing Q.; Ni, Jian; Zhang, Ning; Liao, Hai H.; Tang, Qi Z.; Deng, Wei (Frontiers in Pharmacology, 2017)
Despite therapeutic advances, heart failure-related mortality rates remain high. Therefore, understanding the pathophysiological mechanisms involved in the remodeling process is crucial for the development of new therapeutic strategies. . Andrographolide (Andr), a botanical compound, has potent cardio-protective effects due to its ability to inhibit MAPK. Andr has also been shown to inhibit inflammation and apoptosis, which are factors related to cardiac hypertrophy. Our aim was to evaluate the effects of Andr on cardiac hypertrophy and MAPK activation. Thus, mice were subjected to aortic banding (AB) with/without Andr administration (25 mg/kg/d, orally). Cardiac function was accessed by echocardiography and hemodynamic parameters. Our results showed that Andr administration for 7 weeks decreased cardiac dysfunction and attenuated cardiac hypertrophy and fibrosis in AB mice. Andr treatment induced a strong reduction in the transcription of both hypertrophy (ANP, BNP, β-MHC) and fibrosis related genes (collagen I, collagen III, CTGF, and TGF β). In addition, cardiomyocytes treated with Andr showed a reduced hypertrophic response to angiotensin II. Andr significantly inhibited MAPK activation in both mouse hearts and cardiomyocytes. Treatment with a combination of MAPKactivators abolished the protective effects of Andr in cardiomyocytes. Furthermore, we found that Andr also inhibited the activation of cardiac fibroblasts via the MAPK pathway, which was confirmed by the application of MAPKs inhibitors. In conclusion, andrographolide was found to confer a protective effect against experimental cardiac hypertrophy in mice, suggesting its potential as a novel therapeutic drug for pathological cardiac hypertrophy.